JUMLAH TEMUAN AUDIT ATAS SISTEM PENGENDALIAN INTERN DAN JUMLAH TEMUAN AUDIT ATAS KEPATUHAN TERHADAP OPINI LAPORAN KEUANGAN PEMERINTAH DAERAH - Amalia Nur Alfiani; Sri Rahayu; Annisa Nurbaiti (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2017)
The purpose of examination of financial statements is to provide opinions on the fairness of financial information presented in the financial statements. Based on Law Number 15 of 2004, the criteria for giving opinion are: conformity with Government Accounting Standards, adequacy of disclosure, compliance with laws and regulations, and effectiveness of internal control systems. This study aims to examine the effect of the number of audit findings on the internal control system and the number of audit findings on compliance with the opinion of the financial statements of local governments in West Java. Population in this research is 52 Reports of Result of Inspection on Local Government Financial Report (LKPD) in city/ district in West Java during 2014-2015. The sample in this study is the entire population. The partial test results of the audit findings on the SPI and the number of audit findings on each compliance have no significant effect on LKPD opinion, and simultaneously the number of audit findings on the SPI and the number of audit findings on compliance have no significant effect on the LKPD opinion of the city / district in Java West in 2014-2015.